PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT SOMAMBAWA KABUPATEN NIAS SELATAN - Deniyarni Telaumbanua (Universitas Nias Raya, 2026)
The purpose of this research is to determine the influence of work motivation and work environment on employee performance at the Sombawa sub-district office, South Nias district. The type of research used in this research is associative quantitative research. The data source is the population and the sample in this study was 31 respondents. The data collection technique is to use a questionnaire. The data analysis method used in this research is multiple linear regression analysis. The results of the first partial test research, work motivation on employee performance at the Somambawa sub-district office, show that the value of tcount (2.767) T table (1.701) means that there is a significant influence between work motivation on employee performance at the Somambawa sub-district office, South Nias district. The results of the second partial test, work environment on employee performance, show that the results of T count (2.038) > T table (1.701) have a significant influence between the work environment on employee performance at the Somambawa sub-district office, South Nias district. Simultaneous test results show that Fcount (5.370) > (3.343) means that work motivation and work environment variables simultaneously influence employee performance variables at the Somambawa sub-district office, South Nias district. Suggestions in this research: The leadership of the Somambawa Subdistrict Office, South Nias Regency should continuously provide work motivation to employees in the organization so that they are encouraged and motivated to carry out their work with enthusiasm. The leadership of the Somambawa Subdistrict Office, South Nias Regency needs to pay attention to and improve work facilities such as provision of personal computers, ventilation, fans and work equipment that can support the implementation of work within the organization. Employees of the Somambawa Subdistrict Office, South Nias Regency should carry out their work with enthusiasm and maximize the results of their work well using their abilities. Employee work should be adjusted to the abilities obtained with the aim of improving organizational performance.